The Greek Makhnovists (TEL Tempo, Espaço e Linguagem, 2024)
Abstract: Nick Heath, in this study, discusses the role of Greeks in the Makhnovist movement. The author here describes how troops made up of Pontic Greeks were important in the development of the Revolutionary Insurgent Army of Ukraine (RIAU) and its insurrection. By highlighting some of these Greek figures, Heath demonstrates how they related to the Makhnovist phenomenon from its beginnings to its decline. Keywords: Greek. Makhnovist. Anarchist. Ukraine.